An Exploration of the Metaphors and Images Used to Describe Leadership in Two Different Cultural Contexts - Randell, Shirley; Yerbury, Hilary (Frontiers in Education, 2020)
This paper is developed from qualitative data exploring the metaphors used to describe women’s leadership in differing cultural contexts. Metaphors are a useful communication tool, allowing us to understand an idea or concept through some other phenomenon. Understandably, studies of metaphor tend to focus on metaphors deriving from the English language and from Western cultures. Our everyday language literature abounds with metaphors that evoke images of the masculine - including of machines, war and fighting, competition, games and sport. Leadership is generally thought of as ‘a good thing’, as something important, carried out by people with desirable attributes, such as courage and insight, or with attractive personalities and good communication skills. Metaphors used in discussing women’s leadership in many countries may support this approach, but they do so by highlighting the obstacles women face, for example, the glass ceiling, glass cliff, sticky floors and the labyrinth. This study attempts to break the mould, investigating the understanding of women’s leadership as expressed in metaphors that is contextualized differently across the continents. Taking an interpretive approach, this study seeks to present leadership through the understanding of female leaders involved in the field of education broadly defined, from Rwanda and Bangladesh, who gave accounts of their metaphorical conceptualisation of leadership. Using narrative analysis, these accounts were analysed to identify and interpret the metaphors emerging from descriptions of leadership experiences. The analysis shows that these leaders used metaphors determined by a dynamic interplay of personal, situational, and cultural factors. Somewhat surprisingly, the metaphors used to present leadership are not always based on a local cultural context, with some explicitly including references to European plants, which could be considered exotic. However, they are not metaphors that fit neatly into the taxonomies recognised in the literature. This study makes an important contribution to the literature on leadership, especially leadership in education. It is one of the few studies focussing on the stories of women from a non-Western background. The pool of case studies presented here is limited, but these metaphors represent thinking tools enabling a scholarly and imaginative understanding of women’s leadership in education.